(Captain) America in crisis: popular digital culture and the negotiation of Americanness. Issue 5 (2nd September 2020) - Schmid, Julian
Abstract: This article engages with the contemporary crisis of American identity and how the narratives of the Trump presidency are visually negotiated in the digital world. The Marvel Comics character Captain America has accompanied American identity constructions, crises, and discourses on US foreign policy for almost 80 years. Thus, it is no surprise that Captain America is again popular at a time of increased national crisis, made ever more present as a core character in the major feature film productions of the Marvel Cinematic Universe. In the digital space, Captain America occupies a crucial political position as an easily identifiable visual carrier of identities and values that correspond with the public's concerns. This article interrogates how the circulation of visual narratives of Captain America on Twitter and other digital platforms contributes to a broader discourse about the essence of American identity, values and true 'Americanness' against the backdrop of a fragmented and polarised nation. While (Captain) America's search for the truthful narrative remains futile, understanding this futility can help to discover the discursive reasons for the contemporary crisis.